Inside UiTM's pharmacy program interview: discovering tomorrow's pharmacists / Zakiah Mohd Noordin, Nik Aisyah Najwa Nik Mustaffa Shapri and Syahida Fathiah Ahmad Kamal - Mohd Noordin, Zakiah; Nik Mustaffa Shapri, Nik Aisyah Najwa; Ahmad Kamal, Syahida Fathiah (Faculty of Pharmacy, 2024)
The Faculty of Pharmacy at Universiti Teknologi MARA (UiTM) successfully conducted an interview session for prospective students of the Bachelor's in Pharmacy Program (PH240) from June 20 to 23, 2024. The event, held at the UiTM Selangor Puncak Alam campus, attracted over 1200 applicants eager to join the esteemed program.